A numerical investigation of 3D structural behaviour for steel-composite structures under various travelling fire scenarios. (15th September 2022) - Nan, Zhuojun; Dai, Xu; Chen, Haimin; Welch, Stephen; Usmani, Asif
Highlights: Structural behaviour of a 3D steel-composite structure under various travelling fire scenarios (32 cases) were studied. The applied travelling fire methodology was mass and energy conserved. Solely satisfying the critical temperature and deflection may not guarantee a safe structural design, utilisation should also be examined under travelling fires. Compared with inverse opening factor, fire spread rates and fuel load densities are more critical in identifying the worst travelling fire scenario for the structural response. A "slow" travelling fire with a modest HRR, or a "fast" travelling fire with a high HRR, would both induce significant thermal/structural responses leading to failure depending upon different fire resistence rating. The importance of the concrete slab inclusion into a 3D structural model under travelling fires, in comparison with a 2D structural model without slab was identified. Abstract: In performance-based structural fire engineering, "travelling fires" is being gradually accepted as an important fire boundary condition. However, its application is still limited by uncertainties in the selection of different design travelling fire parameters, resulting from the lack of relevant experimental data and corresponding validated structural finite element models which can be used with advanced travelling fire methodologies, e.g. the Extended Travelling Fire Methodology (ETFM) framework. This paper aims to fill this gap through modelling a prototype steel-composite floor structure (representing a "slice" of a large open-plan office), to investigate its true structural response under a wide range of travelling fire scenarios, with an emphasis on considering the effect of concrete slab in a 3D finite element model, using LS-DYNA. To ensure the credibility of this numerical study, the model was first validated against the experimental data of the structural response from the Veselí Travelling Fire Test. In the parametric studies, 32 cases were examined to investigate the thermal and structural response, related to the selection of key design parameters for travelling fires (i.e. fire spread rates, fuel load densities and inverse opening factors (IOF)); fire protection (i.e. different fire protection schemes and required fire resistance rating (FRR)), and the effect of slab specification (i.e. thicknesses and steel reinforcements). It was found that solely satisfying the critical temperature and deflection criteria for the structural members might not guarantee a sufficient structural design for travelling fire scenarios, and it is suggested that the steel stress utilisation should also be examined. Compared with the IOF, it appears that the selection of fire spread rates and fuel load densities are likely to be more critical in identifying the worst travelling fire scenario for the structural response with fire protection. Moreover, the global structural response under travelling fire is also affected by the combination of fire protection (i.e. equivalent FRR in this paper) and fire spread rate. Under a "slow" travelling fire (e.g. 0.5 mm/s) with increasing FRR, the failure of structural elements during the cooling phase was prevented effectively; however, under a relatively "fast" travelling fire (e.g. 2.5 mm/s, 12.5 mm/s), increasing FRR may not always improve the fire performance of the structure. This work also indicates that steel reinforcement ratio has a greater influence on structural response than slab thickness under travelling fires. Furthermore, the 3D finite element model is very important for structural fire analysis, not only due to the more conservative internal force captured by the 3D model (i.e. reduced by over 80 % on the 2D model in our case) thereby reproducing the collapse triggered by the failure of the connection under fire in general, but also the 3D model was able to better represent the deflection and the "internal force reversal" caused by travelling fires.